(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The wild plants and their products make significant contributions to the human and animal food web and are often a means of survival for millions of poor rural households (Mallick et al., 2020). Many tribes in and around the world are intimately associated with forest for their habitat and ecology.